BUSINESS PURPOSE AS A TAX AVOIDANCE CONDITION IN CORPORATE REORGANIZATIONS - Buffon, Marciano; Silva, Isaías Luz da (PANORAMA OF BRAZILIAN LAW, 2015)
With the approval of the general norm of tax avoidance in the national tax laws, there are several judgments of the Administrative Council of Tax Appeals – Conselho Administrativo de Recursos Fiscais (CARF), which have used a tax avoidance institute of comparative law to consider specific practices resulting from companies’ mergers, splits or amalgamation as abusive tax planning. It is known as the “business purpose doctrine”, which has been running the Counselours of the CARF to establish limits on the exercise of business activity, but still little discussed by the Brazilian doctrine. In summary, this new approach seeks to prevent that corporate transactions of this kind are carried out with the purpose of building a diverse legal reality of the factual, under the cover of legal formalism. The legality in corporate reorganizations focusing on the business purpose theory has been subject of compliance with three basic requirements: the temporality of business, the interdependence of the parties and the normality of the operation. In spite of the controversies regarding the legitimacy of the institute, it is noted that adopting a business purpose test seems plausible, once the institute is identified with the cause of the legal business.